The bear and the piano - Litchfield, David (Clarion Books, Houghton Mifflin Harcourt, 2016)
"A bear finds a piano in the woods, learns to play it, and travels to the big city to become rich and famous, but ultimately discovers that his old friends in the forest back home are still the best audience of all"--